GLP-1 and estrogen conjugate acts in the supramammillary nucleus to reduce food-reward and body weight. (November 2016) - Vogel, Heike; Wolf, Stefanie; Rabasa, Cristina; Rodriguez-Pacheco, Francisca; Babaei, Carina S.; Stöber, Franziska; Goldschmidt, Jürgen; DiMarchi, Richard D.; Finan, Brian; Tschöp, Matthias H.; Dickson, Suzanne L.; Schürmann, Annette; et al.
Abstract: The obesity epidemic continues unabated and currently available pharmacological treatments are not sufficiently effective. Combining gut/brain peptide, GLP-1, with estrogen into a conjugate may represent a novel, safe and potent, strategy to treat diabesity. Here we demonstrate that the central administration of GLP-1-estrogen conjugate reduced food reward, food intake, and body weight in rats. In order to determine the brain location of the interaction of GLP-1 with estrogen, we avail of single-photon emission computed tomography imaging of regional cerebral blood flow and pinpoint a brain site unexplored for its role in feeding and reward, the supramammillary nucleus (SUM) as a potential target of the conjugated GLP-1-estrogen. We confirm that conjugated GLP-1 and estrogen directly target the SUM with site-specific microinjections. Additional microinjections of GLP-1-estrogen into classic energy balance controlling nuclei, the lateral hypothalamus (LH) and the nucleus of the solitary tract (NTS) revealed that the metabolic benefits resulting from GLP-1-estrogen injections are mediated through the LH and to some extent by the NTS. In contrast, no additional benefit of the conjugate was noted on food reward when the compound was microinjected into the LH or the NTS, identifying the SUM as the only neural substrate identified here to underlie the reward reducing benefits of GLP-1 and estrogen conjugate. Collectively we discover a surprising neural substrate underlying food intake and reward effects of GLP-1 and estrogen and uncover a new brain area capable of regulating energy balance and reward. Highlights: Estrogen (E) and GLP-1 interact to reduce body weight, food intake and food reward. This interaction can be localized to supramamillary nucleus (SUM), lateral hypothalamus (LH), and nucleus of the solitary tract (NTS). SUM underlies anorexic, weight loss, and reward effects of GLP-1 and E conjugate. LH underlies only the anorexic and body weight effects the GLP-1 and E conjugate. SUM is a novel brain area capable of exerting effects on energy balance and reward.